TINDAK PIDANA TIDAK MENGGUNAKAN LABEL BERBAHASA INDONESIA PADA BARANG YANG DIPERDAGANGKAN DI DALAM NEGERI OLEH PELAKU USAHA - Kusyanto (The Juris, 2024)
Criminal acts are acts that meet the elements of guilt and against the law that have been stipulated in the law and customary norms that apply in society. The reality in community is that there are many violations of the obligation to use Indonesian language labels on goods traded domestically by business actors. The results showed violations of these provisions both in the form of food and beverages such as rice, sugar, sausages and in the form of non-food such as electronic goods, spare parts, children's toys and others, with empirical evidence in the form of permanent legal force decisions. The purpose of this study is to find the causes of violations of the obligation to use Indonesian language labels on goods traded domestically by business actors. Provisions regulating the obligation of business actors to use Indonesian labels on goods traded domestically are contained in Law Number 8 of 1999 concerning Consumer Protection and Law Number 7 of 2014 concerning Trade. The research concluded that some business actors are not aware of these obligations, do not support government programs and lack of supervision, so it is necessary to continuously socialize the law, effective and fair law enforcement and strict government supervision by involving ministries and other relevant agencies and institutions. The method used is a normative research method and the data are collected by library reseach and analized by qualitative method.